Meningkatkan Kemampuan Menulis Siswa Menggunakan Metode CIRC Mata Pelajaran Bahasa Indonesia di SDN 46/II Sirih Sekapur - Miftahul Jannah Siregar (Pusat Riset dan Inovasi Nasional, 2025)
The study discusses the problem of Improving the Writing Ability of Class II Students Using the Cooperative Integrated Reading and Composition (CIRC) Method for Indonesian Language Subjects at State Elementary School 46/II, Sirih Sekapur Village, Jujuhan District, Bungo Regency, Jambi Province. Based on the results of observations in class II of State Elementary School 46/II, Sirih Sekapur Village, problems were found in writing learning that were not optimal. This is because teachers have not used learning models that attract students' interest in learning to write. The value of summarizing students' writing is still below the KKM. So an effort is needed to improve the low writing ability of students, namely through the application of the CIRC Type Cooperative Learning learning model to class II students of State Elementary School 46/II, Sirih Sekapur Village. This study aims to determine the quality of students' writing skills from the first cycle to the last cycle, to find out the improvement of students' writing skills through the application of CIRC Type Cooperative Learning. This type of research is Classroom Action Research (CAR). The data collection techniques used are observation, tests, interviews, tests and documentation. The technique used to ensure the accuracy of the data is carried out by triangulating sources and techniques. The results of this study indicate that the data obtained in the pre-cycle reached a percentage of 32.53%, cycle I reached a percentage of 64.71% and cycle II reached a percentage of 94.12. From the percentage of student learning outcomes in the pre-cycle, cycle I, and cycle II, it shows that the implementation of Cooperative Learning Type CIRC can improve students' writing skills in learning Indonesian in class II students.